Affairs of the heart : Vol. I [videorecording (DVD)] : classic tales of love and loss based on the fiction of Henry James - Reardon, John, 1938-; Lindsay-Hogg, Michael; Bennett, Derek; Rigg, Diana; James, Henry, 1843-1916; James, Henry, 1843-1916; James, Henry, 1843-1916; James, Henry, 1843-1916 (Distributed by Acorn Media, 2008)
Romantic tales from the late Victorian high society of love and loss. These unfold from the country houses of England to the drawing rooms of New York, from the palazzos of Venice to the art studios of London. Scoundrels and schemers collide with ingénues and admirers in the terribly intricate affairs of the heart.